CITRA DIRI KARTUN INDONESIA Kajian Ilustrasi Grafis pada Garis Wajah Kartun dengan Wayang - Asnar Zacky (Ars: Jurnal Seni Rupa dan Desain, 2008)
It has to be admitted that there is an amazing similarity between the line o f Western Cartoon andWayang Purwa. It is recommended that this universality o f cartoon is used as a feedback to present and tostrengthen the self image o f the Indonesia cartoon.It is urgent to be done immediately before the irony, when the Western people and the Japaneseexplored and developed their cartoon by using inspirations that utterly rooted m Indonesian culture,happens again.Deep awareness o f and full attention given by Indonesian cartoonists to put the root o f Indonesianculture forzvard when they do their creative process is absolutely needed.Keywords: cartoon image, cartoonists’ attention, Indonesian culture root